Implementation of National Vision Character Values Through Islamic Education Learning in Public Senior High School 1 and 11 Garut - Rahayu Kariadinata; Aan Hasanah; Asep Nursobah; Raito Raito (International Journal of Social Service and Research, 2022)
This study examines the inculcation of national vision character qualities using Islamic education learning at Public Senior High School 1 and 11 Garut. This study uses a qualitative approach with analytical descriptive methods to obtain an empirical and objective picture, as well as to analyze a certain phenomenon/condition that is currently happening. Data was collected through observation, interviews, and documentation. The data analysis was carried out by means of data reduction, data presentation, drawing conclusions, and data verification. The results of this study, that: (1) the cultivation of national insight character values in Islamic education learning that is applied to the two schools is effective and optimal, because it is in line with the objectives/competencies of Islamic education learning, methods, teaching materials/materials, tools or media, and evaluation of learning, (2) the programs in the two schools are carried out through several routine programs in order to have awareness of nationalism, (3) the process of inculcating the character values of national insight in these two schools has been carried out well, this is implied by their various patterns of attitudes and behavior when turning on the environment schools, (4) the supporting and inhibiting factors of these two schools consist of internal factors and external factors, and (5) the results of inculcating the character values of national insight in Islamic education learning in these two schools are students having good attitudes and behavior or character.